Предмет: Математика,
автор: школьник9004
памогите с примером
Приложения:
Ответы
Автор ответа:
0
а) -8,3-(-x-8,3)=-8,3+x+8,3=x
б) -(-a-y)+(a-t)=a+y+a-t=2a+y-t
б) -(-a-y)+(a-t)=a+y+a-t=2a+y-t
Автор ответа:
0
Спасибо вам всем
Автор ответа:
0
а) -8.3 + х + 8. 3 = х
б) а + у + а - t = 2a+y-t
б) а + у + а - t = 2a+y-t
Автор ответа:
0
Спасибо вам всем
Похожие вопросы
Предмет: История,
автор: zelentsova12
Предмет: Русский язык,
автор: mgdkgsydsysdidh0
Предмет: Английский язык,
автор: natali4563
Предмет: Алгебра,
автор: Аноним